The virtual class as a knowledge democratization model - Coto Chotto, Mayela (2012)
This paper presents the conceptualization and use of a virtual classroom in the course EIF-200 Fundamentos de Informática, first course in the Information Systems Engineering career of the Universidad Nacional of Costa Rica. The virtual classroom is seen as a complement to the class and is conceived as a space that allows to centralize teaching resources, thereby promoting the  democratization of knowledge among students and teachers. Furthermore, this concept of virtual classroom helps to reduce the culture of individualism, present many times in university teaching practices, and contributes to create new opportunities to learn from other colleagues within a culture of reflection, analysis and respectful dialogue aimed to improve the teaching practices.